2019
DOI: 10.1186/s12879-019-4157-2
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol immunization by alginate coated mycobacterium (BCG/MIP) particles provide enhanced immune response and protective efficacy than aerosol of plain mycobacterium against M.tb. H37Rv infection in mice

Abstract: Background With the aim of preparing a more effective, safe and economical vaccine for tuberculosis, inhalable live mycobacterium formulations were evaluated. Methods Alginate particles in the size range of 2–4 μm were prepared by encapsulating live Bacille Calmette–Guérin (BCG) and “ Mycobacterium indicus pranii” (MIP). These particles were characterized for their size, stability and release profile. Mice were immunized with liquid aerosol or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 51 publications
(42 reference statements)
0
12
0
Order By: Relevance
“…Other lines of research to improve TB vaccination are directed towards addressing mucosal immunization and alternative routes of TB vaccination. In this context, inhalable TB vaccines offer the potential to mimic the natural route of M.tb infection and provide durable mucosal immune responses which may be critical for M.tb control [104,105]. In this regard, intranasal administration of whole cell inactivated MTBVAC HK vaccine in mice, improved the protective efficacy of mice previously vaccinated with subcutanous BCG, by triggering mucosal secretory immunoglobulins [106].…”
Section: Lack Of Educationmentioning
confidence: 99%
“…Other lines of research to improve TB vaccination are directed towards addressing mucosal immunization and alternative routes of TB vaccination. In this context, inhalable TB vaccines offer the potential to mimic the natural route of M.tb infection and provide durable mucosal immune responses which may be critical for M.tb control [104,105]. In this regard, intranasal administration of whole cell inactivated MTBVAC HK vaccine in mice, improved the protective efficacy of mice previously vaccinated with subcutanous BCG, by triggering mucosal secretory immunoglobulins [106].…”
Section: Lack Of Educationmentioning
confidence: 99%
“…The application of biomaterial components in either tissue engineering or vaccine delivery system is known to have adjuvant effects, as measured by the observed enhancement of the host immune response [ 160 , 161 , 162 ]. Encapsulation of BCG and M indicus pranii (MIP) in bio-polymeric alginate microparticles as dry powder aerosol (DPA) were found to provide better protection against M. tuberculosis in a study conducted by Nagpal et al [ 163 ]. The developed formulations were found to be stable at temperatures up to 40 °C after 6 months of storage.…”
Section: Novel Approaches For Dry Powder Inhalable Lung Drug Delivmentioning
confidence: 99%
“…These findings demonstrated that BEAP/MEAP immunized animals have minimal lung pathology as compared to BCG/MIP animals, respectively. In short, alginate-coated BCG/MIP formulated in DPA are very promising vaccine candidates for TB with better protection against M. tuberculosis H37Rv [ 163 ].…”
Section: Novel Approaches For Dry Powder Inhalable Lung Drug Delivmentioning
confidence: 99%
“…Dry powder-based vaccine formulations have been designed and pre-clinically tested against several infectious diseases, progressing into clinical trials (Table 1). An inhalable vaccine formulation of alginate-coated live Mycobacterium microparticles was more immunogenic than liquid aerosols, and provided better protection in mice against experimental Mycobacterium tuberculosis infection [27]. In another study, an intrapulmonary-delivered Advax-adjuvanted influenza vaccine induced higher memory B and T cell responses than intranasal or intramuscular immunisation and conferred superior disease protection [28].…”
Section: Dry Powders For Pulmonary Immunisationmentioning
confidence: 99%